TOPOGRAPHICAL AND HISTOLOGICAL STRUCTURE OF DUCTUS EPIDIDY MIDS OF COMMON QUAIL ( Coturnix. c. coturnix L.) - Al-Samarrae*, N. S.; Al-Jobori, KH. A.; Al-Hathry, KH. A.; F., Al-Shamary. B. (The Iraqi Journal of Veterinary Medicine, 2000)
The epididymal region of the common quail was located on the dorso-medial aspect of the testis, extending from cranial pole to the caudal pole of the testis and connected the urodeum via the vas deferens and the receptaculum. The ductus epididymidis in common quail showed a series of coiled ductules which were closely bounded to the testis by connective tissue. The lining epithelium of these ductules were ciliated columnar epithelium, but non ciliated columnar epithelium were also noticed.